Cinema Edukasi: Program Pemutaran Film sebagai Media Penguatan Nilai Karakter Kebangsaan pada Anak - Muh. Herisman; Riskawati Riskawati (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
Character education is the main foundation in shaping the personality and identity of the nation's children from an early age. This community service activity aims to strengthen national character values ​​through educational films that are engaging and appropriate for children. The program, titled Educational Cinema, uses the film Nussa: